Structure and catalytic activity of ultrasmall Rh, Pd and (Rh + Pd) nanoparticles obtained by mediated electrosynthesis. (13th February 2019) - Yanilkin, Vitaliy V.; Nastapova, Natalya V.; Nasretdinova, Gulnaz R.; Osin, Yury N.; Evtjugin, Vladimir G.; Ziganshina, Albina Yu.; Gubaidullin, Aidar T.
Abstract : Efficient mediated electrosynthesis of catalytically active ultrasmall mono- and bimetallic nanoparticles of Rh, Pd stabilized with CTAC was carried out in water. Abstract : Efficient electrosynthesis of ultrasmall spherical mono- and bimetallic nanoparticles (NPs) of Rh and Pd stabilized in the shell of cetyltrimethylammonium chloride (CTAC) in the solution bulk was carried out by methylviologen (MV) mediated reduction of equimolar amounts of Pd(ii ) and Rh(iii ) (1.5 mM) in the presence of CTAC (10 mM) at controlled potentials of the MV 2+ /MV˙ + redox couple in a water/0.1 M NaCl medium at room temperature. Similar electrosynthesis of RhNPs also effectively proceeds when poly( N -vinylpyrrolidone) (10 mM) is used as a stabilizer. Metal ions are quantitatively converted to NPs upon consumption of the theoretical amount of electricity. Sizes of isolated PdNPs and RhNPs are 4.6 ± 0.9 nm and 1.7 ± 0.3 nm, respectively. Bimetallic (Pd, Rh)NPs were obtained by three procedures: (i) preliminary synthesis of RhNPs followed by reduction of Pd(ii ) ((Rh/Pd)NPs, 2.2 ± 0.7 nm); (ii) preliminary synthesis of PdNPs followed by reduction of Rh(iii ) ((Pd/Rh)NPs, 4.9 ± 1.0 nm); (iii) joint reduction of Pd(ii ) and Rh(iii ) ((Pd–Rh)NPs, 3.1 ± 0.5 nm). In all cases, solid-solution alloy (Pd, Rh)NPs are obtained. In an aqueous medium, all the NPs obtained are catalytically active in the hydrogenation of p -nitrophenol with sodium borohydride to p -aminophenol, but their use in the Suzuki coupling reaction of iodobenzene with phenylboronic acid does not lead to the target product. An increase in the CTAC concentration by 7.5 times leads to an increase in the catalytic activity of PdNPs in both types of reactions.